Impact of personality psychology and burnout on job performance among accounting educators in public universities in Malaysia - Liou, Wei Hau (2016)
As time pass by, the role of professional accountant has become wider by involved in a more challenging environment that have a direct or indirect impact on the country’s economy and future development. The increase of corporate scandal and ethical issues associated with educator’s performance implied for higher education institutions as education is a complex route that demanding on human qualities not quantity. Its worldview that education is the most powerful tool in the world that capable to molding student’s attitudes and influence the direction of a future accountant. Accounting educator plays an important role during the process, to restore human well-being which upholding the terms of internal valuefrom inside-out and spirit of the law. Education institution has the ability to guide and nurture future corporate leader as human leader, it was due to education ruins as the only rescue anchor that able to direct accounting student towards a rehabilitation of internal value. Unfortunately, lecturer required to fulfil the Key Performance Indicators (KPIs) such as number of journal publications, research support, professional presentations / conferences, courses taught professional service and college or university service in return to meet the qualifications or job security. Therefore, this research undertaken highlighted the personality psychology of accounting educator that comprises of psychological ownership, self-efficacy, empathy and spirituality are deeply connected to the educators’ job performance. Burnout added into this research due to the increase of workload as part of fulfilment the Key Performance Indicator setting by either faculty, university or government. This study was carried out among the accounting educator from 12 public university that offering accounting education in Malaysia and questionnaires were distributed through online and paper survey. Ninety-nine of the accounting educator were participated in this study. This study using both actual and perceived job performance rating to measured job performance as a multidimensional construct with three dimensions (Research support, Professional services, and Instructional support and journal publication). The analysis reveals that self-efficacy and empathy being positively significant towards the job performance dimension. In terms of burnout mediate personality psychology with actual job performance, burnout does not show a significant relationship between both variables while finding indicates self-efficacy and spirituality have a negative relation to burnout. Theoretically, this research depicts a mechanism to improve job performance of accounting educators in Malaysian public universities as well as recommend the administrators to include personality tests in recruiting staff as there is no one size fits all. The essence of ideological education should rests in adopting different approaches to cater different kinds of individuals and build on the foundation that lies on daily practice. Meanwhile, the academic curriculum should aims at mentality development and achieve of wholesome character.